Süddeutsche Hofkapellen im 18. Jahrhundert - Leopold, Silke; Bärbel, Pelker (Heidelberg University Publishing (heiUP), 2021)
Since the Middle Ages, next to churches the courts have been the most important employers of professional musicians. The important role of court music in European and particularly in German music history has not been reflected in the efforts made by musicological scholarship in the past. Although there are numerous studies on particular courts, comparative studies are still lacking. This publication documents the current state of research on the most important court chapels, as well as selected smaller aristocratic chapels in southern Germany during the eighteenth century.